Sex and β-Endorphin Influence the Effects of Ethanol on Limbic Gabra2 Expression in a Mouse Binge Drinking Model - Rhinehart, Erin M.; Nentwig, Todd B.; Wilson, Diane E.; Leonard, Kiarah T.; Chaney, Bernie N.; Grisel, Judith E. (Frontiers in Genetics, 2018)
Binge drinking is a widespread problem linked to increased risk for alcohol-related complications, including development of alcohol use disorders. In the last decade, binge drinking has significantly increased, specifically in women. Sexually dimorphic effects of alcohol have been well-characterized in the clinic, however, the underlying mechanisms for sexual dimorphisms in the physiological and behavioral effects of alcohol are poorly understood. Among its many effects, alcohol consumption reduces anxiety. Female mice that do not produce β-endorphin (βE), an endogenous opioid peptide, have an enhanced anxiety-like phenotype, and increased consumption of alcohol. Because alcohol-mediated anxiolysis depends upon stimulation of the inhibitory neurotransmitter, GABA, and βE is involved in GABA signaling to reduce anxiety, we sought to determine whether βE affects sexually dimorphic binge drinking behavior by affecting CNS Gabra2 expression. To test this hypothesis we used βE knock-out mice in a “drinking in the dark” model where adult male and female C57BL/6J controls (βE +/+) and βE deficient (βE -/-; B6.129S2-Pomctm1Low/J) mice were either provided with one bottle of 20% ethanol (EtOH) and one of water (EtOH drinkers) or 2 bottles of water (Water drinkers) 3 hours into the dark cycle for 4 consecutive days. Following the binge test on day 4, limbic tissue was collected and frozen for subsequent qRT-PCR analysis of Gabra2 mRNA expression. Water-drinking βE +/+ females expressed more Gabra2 in Central Nucleus of the Amygdala and the Bed Nucleus of the Stria Terminalis than male counterparts, but this sex difference was absent in the βE -/- mice. Genotype had no effect on either alcohol consumption or drug-induced increase in Gabra2 expression. In contrast, βE expression had bi-directional effects in females: in wildtypes Gabra2 mRNA was reduced by binge EtOH consumption, while EtOH increased expression in βE -/- females to levels commensurate with drug-naïve βE +/+ females. These results support the contention that βE plays a role in sexually dimorphic binge-like EtOH consumption, perhaps through differential expression of GABAA 2 subunits in limbic structures involved in stress and anxiety.